Nationwide incidence of motor neuron disease using the French health insurance information system database. Issue 5 (3rd July 2017) - Kab, Sofiane; Moisan, Frédéric; Preux, Pierre-Marie; Marin, Benoît; Elbaz, Alexis
Abstract: Objective : There are no estimates of the nationwide incidence of motor neuron disease (MND) in France. We used the French health insurance information system to identify incident MND cases (2012–2014), and compared incidence figures to those from three external sources. Methods : We identified incident MND cases (2012–2014) based on three data sources (riluzole claims, hospitalisation records, long-term chronic disease benefits), and computed MND incidence by age, gender, and geographic region. We used French mortality statistics, Limousin ALS registry data, and previous European studies based on administrative databases to perform external comparisons. Results : We identified 6553 MND incident cases. After standardisation to the United States 2010 population, the age/gender-standardised incidence was 2.72/100, 000 person-years (males, 3.37; females, 2.17; male:female ratio = 1.53, 95% CI1.46–1.61). There was no major spatial difference in MND distribution. Our data were in agreement with the French death database (standardised mortality ratio = 1.01, 95% CI = 0.96–1.06) and Limousin ALS registry (standardised incidence ratio = 0.92, 95% CI = 0.72–1.15). Incidence estimates were in the same range as those from previous studies. Conclusions : We report French nationwide incidence estimates of MND. Administrative databases including hospital discharge data and riluzole claims offer an interesting approach to identify large population-based samples of patients with MND for epidemiologic studies and surveillance.